2017
DOI: 10.1186/s12879-017-2341-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the immunogenicity and safety of different doses and formulations of a broad spectrum influenza vaccine (FLU-v) developed by SEEK: study protocol for a single-center, randomized, double-blind and placebo-controlled clinical phase IIb trial

Abstract: BackgroundCurrent influenza vaccines, based on antibodies against surface antigens, are unable to provide protection against newly emerging virus strains which differ from the vaccine strains. Therefore the population has to be re-vaccinated annually. It is thus important to develop vaccines which induce protective immunity to a broad spectrum of influenza viruses. This trial is designed to evaluate the immunogenicity and safety of FLU-v, a vaccine composed of four synthetic peptides with conserved epitopes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Some of the candidates used in clinical trials show the possibilities in the decreasing Influenza infection (Sebastian and Lambe 2018 ; Sautto et al 2018 ; Nachbagauer and Palese 2019 ). However, vaccine candidates which are currently in use at clinical studies are aimed to elicit an antibody response against more conserved Influenza proteins (Doorn et al 2017a , 2017b ). Furthermore, the limitations of currently in market seasonal Influenza vaccines and the persistent threat of future pandemics have made it necessary for novel vaccine design.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the candidates used in clinical trials show the possibilities in the decreasing Influenza infection (Sebastian and Lambe 2018 ; Sautto et al 2018 ; Nachbagauer and Palese 2019 ). However, vaccine candidates which are currently in use at clinical studies are aimed to elicit an antibody response against more conserved Influenza proteins (Doorn et al 2017a , 2017b ). Furthermore, the limitations of currently in market seasonal Influenza vaccines and the persistent threat of future pandemics have made it necessary for novel vaccine design.…”
Section: Discussionmentioning
confidence: 99%
“…To address this need, influenza research over the past decade has focused on the discovery of new (universal) antigenic targets and improved vaccine modalities. Among the latter, those that have progressed into clinical trials are viral vectors, plasmid DNA ([ 97 ] and more), recombinant proteins [ 98 , 99 ], and polypeptide epitope sequences [ 100 , 101 , 102 ]. The focus of this review has been on viral vectors and their potential as strong candidates for protective influenza vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, FLU-v, developed by PepTcell (SEEK), is a peptide vaccine comprised of four synthetic peptides with conserved epitopes from influenza A and B strains designed to provide a broadly protective cellular immune response against influenza A and B. Results from phase IIb clinical trials showed that adjuvanted FLU-v recipients ( n = 40) were significantly less likely to develop mild to moderate influenza disease (MMID) following intranasal challenge of A/CA04/H1N1 vs. placebo ( n = 42) (32.5 vs. 54.8% p = 0.035) [ 69 , 70 , 71 ]. Nevertheless, overall the vaccine protection effect was poor.…”
Section: Novel Universal Influenza Vaccinesmentioning
confidence: 99%